Studi Komparatif Konsep Kenabian Perspektif Al-Farabi Dan Al-Razi - Azar, Ahmad Zarkasyi Noor Wahid (Mazalat: Jurnal Pemikiran Islam, 2025)
Many Muslim thinkers, such as Al-Farabi and Al-Razi, have paid attention to the concept of prophecy in Islamic philosophy, which is a complex issue. Al-Farabi, a Muslim philosopher from the 10th century, argued that prophecy was a higher form of knowledge given to selected people to lead society towards goodness and happiness. He views prophets as bridges between divine revelation and human rational understanding. On the other hand, Al-Razi emphasized that the teachings of the prophets must be rationally acceptable and beneficial to humans. He also emphasized that although reason has limitations, reason is still important because faith and revelation are called to function. Despite differences of opinion, Al-Farabi and Al-Razi agree that prophecy is not just a spiritual phenomenon that must be understood and accepted rationally by humans. They also agree about the moral role of prophets and how important reason and intuition are for understanding prophecy.